Forming continuity and stability in contemporary Islamic architecture from the architectural concepts of the Islamic world - Awawda, Hasan M.I (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2014)
Contemporary Islamic architecture is created from the process of interaction between the authenticity of Muslim heritage with technology, in addition to meeting the progress of the continuous humanitarian requirements in architecture. However, the dilemma of the contemporary architectural translation of this interaction resides in focusing on the mere formation of Islamic architecture and copying its traditional elements, without investigating its essence. In consequence, contemporary Islamic architecture is being driven to a state of rigidity, and it is being deprived from its spirit and vitality. Thus, in order to rid contemporary Islamic architecture of this situation, and to highlight the depth of Islamic architecture and its essence, this study presents a new process of forming the architectural correlation that depends on the relations between the continuity of technology and the stability of the essence of Islamic architecture, through its static valuable combination. The guidelines and the proposed process of forming in this study have been investigated in three stages, namely investigating the philosophical indications of continuity and stability, investigating their combined values in term of Islamization, and investigating it in term of moderation and in term of the common human product. Whereas, the second stage grasped five values of continuity and stability through analysing traditional and contemporary case studies (Value of Privacy, Spirituality, Coexistence with Nature, Transparency and the value of accumulation or motion). While the third stage represents the process of converting these values into architectural relations with their artistic and philosophical indications through architectural examples that can be considered sources of the proposed relations. This study presents philosophical guidelines of contemporary Islamic architecture. In addition, it redefines the relations of continuity and stability, the essence of Islamic architecture, and redefines the philosophical and architectural combined formation of continuity and stability.